Molecular species composition of polar lipids from two microalgae Nitzschia palea and Scenedesmus costatus using HPLC-ESI-MS/MS - Mazzella,Nicolas; Fadhlaoui,Mariem; Moreira,Aurélie; Morin,Soizic (PeerJ Analytical Chemistry, 2023)
This study examines the polar lipid profiles of two freshwater algae, Scenedesmus costatus and Nitzschia palea. HILIC-ESI-MS/MS analysis was used to determine and quantify the major phospholipids and glycolipids, as well as their relative molecular species, extracted from the two microalgal cultures. Glycolipids were eluted first, followed by phospholipids partially co-eluting with a sulfoglycolipid. The fragmentation pattern in the negative ionization mode for galactolipids was studied, revealing the stereospecific distribution of fatty acids on the glycerol backbone. Green algae frequently include 18:3 fatty acid in both phospholipids and galactolipids, while monogalactosyldiacylglycerol (MGDG) and digalactosyldiacylglycerol (DGDG) were more saturated and contained shorter acyls. The diatom phospholipids contained mainly molecular species with saturated or monounsaturated fatty acids, while MGDG and DGDG exhibited a higher proportion of polyunsaturated fatty acids, such as the unique and abundant MGDG (20:5/20:2).
Keywords: Glycolipids; Phospholipids; Fatty acids; Mass spectrometry; Diatoms; Chlorophyta; Freshwater